OPTIMIZATION OF TREATMENTS IN IMPLANTOLOGY BASED ON ARTIFICIAL INTELLIGENCE - Vlad-Ștefan Proca; Mădălina Pavel; Babușca Răzvan; Tibeica Andreea; Stratulat(Mihai) Dana Nicoleta; Norina Forna (Romanian Journal of Medical and Dental Education)
Implant dentistry is a specialized field within dentistry that focuses on the placement and restoration of dental implants.The integration of artificial intelligence (AI) in implant dentistry has brought about transformative advancements in treatment planning, surgical procedures, and post-operative care. The use of AI in implant dentistry has demonstrated the potential to enhance treatment outcomes, minimize errors, and personalize patient care.